Primary production and nitrogen assimilation rates from bay to offshore waters in the oyashio-kuroshio-Tsugaru Warm Current interfrontal region of the northwestern north Pacific Ocean. (October 2020) - Shiozaki, Takuhei; Tada, Yuya; Fukuda, Hideki; Furuya, Ken; Nagata, Toshi
Abstract: We examined primary production (PP) and the assimilation rates of nitrate (ρNO3 - ), ammonium (ρNH4 + ) and dinitrogen (ρN2 ) using 13 C and 15 N tracer techniques along bay to offshore transects in the Oyashio-Kuroshio-Tsugaru Warm Current interfrontal region in the northwestern North Pacific Ocean, during five research cruises covering a full seasonal cycle. Surface inorganic N was depleted in the bays and the offshore region from summer to fall, but the higher particulate organic carbon (POC)/particulate nitrogen (PN) ratio and higher maximum N assimilation rate observed kinetics experiments in the bays suggest that N limitation was stronger in bays than offshore. PP (295–19, 200 nmol C L −1 d −1 ), ρNO3 - (9.45–650 nmol N L −1 d −1 ) and ρNH4 + (11.6–494 nmol N L −1 d −1 ) in the surface waters were generally low in summer and high in spring. Different from the cases of ρNO3 - and ρNH4 +, ρN2 was high (up to 12 nmol N L −1 d −1 ) in mid-summer, especially in offshore regions, and moderate or low (≤2.26 nmol N L −1 d −1 ) during other seasons. N2 fixation largely contributed to total new production (up to 29%) in mid-summer. The mean f -ratio, estimated as the ratio of (ρNO3 -  + ρN2 ) to (ρNO3 -  + ρN2  + ρNH4 + ) at two offshore stations varied within the range of 0.29–0.83 (mean 0.54 ± 0.20). Comparison of the PP and total N assimilation (ρNO3 -  + ρN2  + ρNH4 + ) indicated that the ratio of C to N assimilation rates (max. 95) far exceeded the Redfield ratio (6.6). This finding suggests that other sources of N (e.g., dissolved organic nitrogen) contributed significantly to total N assimilation; if this is correct, the estimated f -ratio may be too high. Alternatively, the f C -ratio was estimated from the ratio of (ρNO3 -  + ρN2 ) to PP by assuming the Redfieldian assimilation ratio, and it ranged from 0.06 to 1.10 (mean 0.45 ± 0.31). Despite uncertainties in both the f - and f C -ratio estimation, our data provide evidence that a large fraction of PP is potentially available for export to deep waters and to higher trophic levels in the interfrontal region of the western North Pacific. Highlights: N2 fixation contributed max. 29% to new production in this interfrontal region. The maximum new production and f -ratio were at the high end of values in the Pacific. Nitrogen limitation was stronger in the Sanriku bays than offshore.